Transient expression of recombinant S1 protein of Porcine Epidemic Diarrhea Virus in Nicotiana benthamiana - Thuong, Ho Thi; Ngoc, Le Thu; Giang, Nguyen Thu; Vy, Trinh Thai; Hoang, Phan Trong; Ngoc, Pham Bich; Trang, Vu Huyen; Ha, Chu Hoang (Vietnam Journal of Biotechnology, 2021)
Porcine Epidemic Diarrhea (PED) is an infectious disease with high mortality especially in suckling piglets. Among the structural proteins of Porcine Epidemic Diarrhea Virus (PEDV), the S protein (including sub-domain S1 and S2), is a homotrimer protein that plays an important role in attaching the viruses to the cell receptors. In particular, the S1 protein is considered as an important sub-component in the development of effective vaccines against PEDV. In this study, for the purpose of expressing S1 in the original form of trimmer and oligomer of trimer based on S-tag and S-protein interactions, the DNA encoding for S1 protein was fused with GCN4pII or GCN4pII-Stag, was then inserted to the pRTRA cloning vector under the control of the 35S CaMV promoter. After that, the whole cassete was inserted into the pCB301 vector and transformed into Agrobacterium tumefaciens for transient expression on Nicotiana benthamiana. The expression of recombinant S1 proteins in tobacco was determined by Western blot. The results showed that the expression levels of S1 trimer and S1 trimer S-tag proteins were equal in plants, which also indicated that S-tag fusion did not affect the expression level of the S1 protein. However, the expression level of S1 proteins was relatively low, reaching 0.005% of total soluble protein. In addition, the expression of S1 trimer S-tag protein and Sprotein-tp protein by co-transformation of two A. tumefaciens strains containing corresponding vectors in plants were also determined by Western blot. This is a premise study for the development of subunit vaccines in plants that prevent the spread of PEDV.